Genome Sequence of the Thermotolerant Foodborne Pathogen Salmonella enterica Serovar Senftenberg ATCC 43845 and Phylogenetic Analysis of Loci Encoding Increased Protein Quality Control Mechanisms - Scott V. Nguyen (American Society for Microbiology, 2017)
ABSTRACT Salmonella enterica subsp. enterica bacteria are important foodborne pathogens with major economic impact. Some isolates exhibit increased heat tolerance, a concern for food safety. Analysis of a finished-quality genome sequence of an isolate commonly used in heat resistance studies, S. enterica subsp. enterica serovar Senftenberg 775W (ATCC 43845), demonstrated an interesting observation that this strain contains not just one, but two horizontally acquired thermotolerance locus homologs. These two loci reside on a large 341.3-kbp plasmid that is similar to the well-studied IncHI2 R478 plasmid but lacks any antibiotic resistance genes found on R478 or other IncHI2 plasmids. As this historical Salmonella isolate has been in use since 1941, comparative analysis of the plasmid and of the thermotolerance loci contained on the plasmid will provide insight into the evolution of heat resistance loci as well as acquisition of resistance determinants in IncHI2 plasmids. IMPORTANCE Thermal interventions are commonly used in the food industry as a means of mitigating pathogen contamination in food products. Concern over heat-resistant food contaminants has recently increased, with the identification of a conserved locus shown to confer heat resistance in disparate lineages of Gram-negative bacteria. Complete sequence analysis of a historical isolate of Salmonella enterica serovar Senftenberg, used in numerous studies because of its novel heat resistance, revealed that this important strain possesses two distinct copies of this conserved thermotolerance locus, residing on a multireplicon IncHI2/IncHI2A plasmid. Phylogenetic analysis of these loci in comparison with homologs identified in various bacterial genera provides an opportunity to examine the evolution and distribution of loci conferring resistance to environmental stressors, such as heat and desiccation.